LITERATURE REVIEW ANALYSIS OF FACTORS THAT CAUSE ABORTION IN PREGNANT WOMEN - Nur Irbah, Wahyu; Lumban Gaol, Marisa; Kesuma Wardani, Elda; Manik, Nurhati; Novita sari, Sonia (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Abortion remains one of the major maternal health issues that can increase maternal morbidity and mortality. Its occurrence is influenced by various factors related to the mother, the fetus, or the environment. This study analyzed the causes of abortion in pregnant women based on published research findings. A literature review was conducted by examining scientific articles retrieved from electronic databases according to predefined inclusion and exclusion criteria. The data were analyzed descriptively to identify factors associated with abortion. The results identified key contributing factors: maternal age (≤20 years or ≥35 years), parity, prior history of abortion, anemia, comorbid conditions, infections, poor nutritional status, and inadequate prenatal care (ANC). Fetal chromosomal abnormalities also represent a significant cause of abortion. The occurrence of miscarriage is influenced by various maternal and fetal factors, with maternal age, history of miscarriage, and maternal health status being the most dominant determinants. Early identification of risk factors and improvement in the quality of prenatal care are essential to reduce the incidence of miscarriage